Effect of hydroxy gas addition on performance and exhaust emissions in variable compression spark ignition engine. (2020) - Murali Krishna, V.; Haritha Reddy, A.; Sandeep Kumar, M.; Raghu, A.
Abstract: Due to increase in the usage of fossil fuels and the various engine emissions which are polluting the environment, it is necessary to go for an alternative method to meet the scarcity of fuels and to reduce the emissions. Expert studies indicate the use of hydroxy gas produced using water by electrolysis in petrol/diesel engine can be the solution for the integrated problem of depletion of hydrocarbon fuels and exhaust emissions. This study mainly deals with the outcome of adding hydroxy gas to gasoline on the performance of variable compression gasoline engine and engine emissions. Currently hydroxy gas is generated in a leakage proof Plexiglas generator with potassium hydroxide electrolyte and is attached to a 4-stroke water cooled variable compression gasoline engine. The results from the experimental study conducted on the engine for compression ratios ranging from 7 to 10 shows a decrease in the total fuel consumption and an increase in brake thermal efficiency due to increase in velocity flame propagation assures complete fuel combustion and permits the engine to be operated at lean ranges. Also the exhaust emissions CO2, CO, O2, HC and NOx are measured by hydroxy gas addition to gasoline and without it